Certolizumab Trough Levels and Antibodies in Crohn Disease: A Single-Center Experience. Issue 3 (17th May 2021) - Ramos, Guilherme Piovezani; Al-Bawardy, Badr; Braga Neto, Manuel Bonfim; Bledsoe, Adam C; Quinn, Kevin P; Heron, Valérie; Willrich, Maria Alice V; Johnson, Amanda; Chedid, Victor G; Coelho-Prabhu, Nayantara; Kisiel, John B; Papadakis, Konstantinos A; et al.
Abstract: Background: Certolizumab pegol (CZP) has been successfully used for the treatment of Crohn disease (CD); however, real-world data regarding the utility of CZP trough levels (CTLs) are lacking. We aimed to correlate CTL with CD outcomes and to determine frequency of CZP antibodies. Methods: Retrospective evaluation of all CD patients on maintenance CZP with CTL obtained between 2016 and 2019. Outcomes included: median CTL, presence of anti-CZP antibodies, biochemical response (BR), clinical response (CR), radiologic response (RR), radiologic healing (RH), and mucosal healing (MH). Results: Seventy-seven CD patients were included. Median CTL was 18.9 µg/mL (interquartile range, 7.6–35.4). Twenty-three patients (27.3%) had positive antibody levels, with lower median CTL compared to patients with no antibodies (0.0 vs 29.8; P < 0.0001). Median CTL levels were higher in patients with vs without CR (30.4 vs 10.3 µg/mL; P = 0.0015) and RR (29.6 vs 5.8 µg/mL; P = 0.006). CZP dosing at least every 2 weeks was associated with higher odds of achieving MH (odds ratio, 3.2; 95% confidence interval, 1.03–9.97). CTL resulted in change in clinical management in 62.7% of cases and presence of CMZ antibodies was associated with an odds ratio of 5.83 (95% confidence interval, 1.57–21.73) of change in management. Receiver operating characteristic curve and quartile analysis suggested that CTL >19 µg/mL is associated with increased rates of CR and RR. Conclusions: Higher CTL was significantly associated with CR and RR. The rate of CZP antibodies was 27.3%. Our data suggest maintenance CTL of ≥19 µg/mL should be achieved in order to optimize outcomes in clinical practice. Lay Summary: Measuring blood levels of certolizumab pegol may improve control of Crohn disease. One third of patients receiving this medication have developed antibodies against it, resulting in lower circulating drug levels. A level >19 µg/mL was associated with better treatment results.